Stable walking dynamics in a semipassive biped (2018)
Semi-passive biped robots have been proposed to achieve efficient and robust bipedal locomotion, based on their natural dynamics. In this work, a compass biped with arc shape feet, actuated by a rocker mechanism on the hip is presented and studied. Initially, the effects of the variation of the excitation frequency and amplitude on the stability of the walking cycle are determined. Both, simulation results and experimental tests, suggest that, for a given range of excitation frequencies, the robot exhibits attractive equilibrium as well as entrainment. In addition, strategies for startup, turning and stopping of the robot were explored, obtaining promising results. This work supports the possibility of developing a controllable underactuated robot with a comparatively low cost of transport.